Chances of consolidation the financial sector in Iraq according to GATS agreement and World Trade Organization - حميد عمار محمود; كاظم محمد حسين; هداب سرمد عبد الجبار (Journal of Economics and Administrative Sciences, 2025)
This research focuses on necessary state to develop and strong the financial sector in Iraq by consider that it is allow to achieve the financial flexibility and the enough currency to encourage the investment and economic growth , this picture will be coming by take and obligation the international criteria by general agreement on trade in services (GATS) that it is one of agreements of world trade organization (WTO). This mater doing to strong the legal and legislation environment founded international confidential , by it , the institutions and financial sector in Iraq will be more active.